Pharmacokinetics of Conventional and Long-Acting Oxytetracycline Preparations in Kilis Goat - Aktas, İbrahim and Yarsan, Ender (Frontiers in Veterinary Science, 2017)
The pharmacokinetics of conventional and long-acting (LA) oxytetracycline (OTC), widely used broad-spectrum antibacterial drugs in veterinary medicine, were evaluated in Kilis goats at single dosage of 20 mg/kg body weight (bw). A total of 21 goats were divided into three groups: intravenous (Group I) and intramuscular (IM) (Group II) administration of the conventional formulation and IM administration of the LA formulation (Group III). Blood samples were taken at 0.25, 0.5, 1, 2, 4, 8, 12, 24, 36, 48, 60, 72, and 96 h; and OTC analysis was performed by HPLC. For Group III and Group II, time to reach maximal plasma drug concentration (Tmax) was 0.6 ± 0.28 and 0.46 ± 0.09 h and maximal plasma drug concentrations (Cmax) were 8.72 ± 2.47 μg/ml and 13.57 ± 5.83 μg/ml, respectively. In Group I, C0 concentration was found to be 63.51 ± 11.59 μg/ml. The elimination times (T1/2) were 10.84 ± 3.20, 27.96 ± 11.66, and 10.47 ± 1.30 h; and AUC were 115 ± 29.12, 96.44 ± 9.49, and 80.86 ± 12.76 μg/ml/h for Group I; Group II, and Group III, respectively. Bioavailability by IM administration were 69.71% for the conventional OTC and 83.15% for the LA OTC.